Strategy of Islamic Religious Education Teachers to Prevent Radicalism from Emerging at SMP Muhammadiyah 12 GKB Gresik - Putra, Eksa Dwiandra; Bakhruddin, Muhammad; Hayumuti, Hayumuti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Islamic religious education teachers have a responsibility to disseminate a true understanding of the faith, which does not compromise on the values of diversity and nationality. This is necessary to avoid radical teachings that can create tension between Muslims and other religious groups, as well as acts of violence carried out in the name of religion. Problem formulation How Islamic Religious Education teachers understand the issue of radicalism among students, What are the strategies of Islamic Religious Education teachers in preventing radicalism, What is the effectiveness of the strategies used by Islamic Religious Education teachers in preventing and overcoming radicalism among students, What are the supporting and inhibiting factors of Islamic Religious Education teachers in preventing radicalism, The research aims to illustrate about, Teacher Strategies Islamic Religious Education in preventing students' understanding of radicalism with a qualitative method approach. Strategies used by Islamic Religious Education teachers in preventing radicalism values include, providing education to students about radicalism and its dangers, habituation through religious activities, getting used to empathizing with others, instilling love for religion and the homeland, and strengthening tasamuh and tarahum attitudes. The impact of the implementation of Islamic Religious Education teachers' strategies in preventing radicalism values in students includes, students' insight into radicalism increases, students' character education becomes stronger, the formation of empathy and social awareness, and the attitude of tasamuh and tarahum among students increases.